REPRESENTASI USIA IDEAL PERNIKAHAN DALAM IKLAN TELEVISI (Kajian Semiotik Tentang Iklan KB Versi Televisi Episode “Pernikahan Dini”) - Haryono, Cosmas Gatot (Universitas Bunda Mulia, 2015)
The fall of the Suharto government coupled with changes and reforms in various fields apparently it does not touch the family planning program. BKKBN noted, the population growth rate after the reform uncontrollable. Early marriage which contributed to high birth rate compared to previous years. Today, the government began to realize and seek to return the brakes on population growth rate, which until now at 2.6 percent. BKKBN various campaigns conducted through various media. One of the themes compelling ads and according to the researchers studied is a theme suited for early marriage. Advertising on television is about the love of a young woman who was rejected by his idol because of problems young age. The boy's love was finally accepted after he finish school and get a job. In this study, researcher used a qualitative research method with a semiotic approach to determine the meaning or message is behind the ad. Data collection method in this paper is a method of documentation, while the method of data analysis used in this paper is the method of semiotic analysis with a semiotic analysis is based on the theory of Roland Barthes, the meaning of the signified, signifier, denotation, connotation, and mythology. Results from this study revealed that the ad about KB represents marriage as an important step in life that must be prepared carefully. Not only is the right age factor alone, but more than that marriage must be accompanied by a readiness partner in terms of economic, health, and the future of generations in denotations and connotations. Proper preparation will only be obtained at the age that had been